الاصلاحات الاقتصادية كمدخل للتنمية المستدامة في الجزائر للفترة 1990 ــ 2010 - دمدوم, زكريا; بلقاسم شيخة, خليفة (جامعة الوادي - University of Eloued, 2014)
إن موضوع التنمية الإقتصادية، نال حيزا كبيرا من الاهتمام بهدف معرفة مصادرها، واساليب تحقيقها وكيفية استدامتها والعوامل المدعمة لها وعلاقتها بالإصلاحات الاقتصادية. تعززهذا الاهتمام، بعد تبني غالبية الدول النامية للتحول من الاقتصاد المركزي الى اقتصاد السوق كبديل لتحقيق التنمية القابلة للاستمرار، وبمرور الوقت ظهرت السياسات والبرامج الاقتصادية المرتبطة بأزمة الديون الخارجية منذ سنة 1982 من خلال اعلان المكسيك وبعض دول امريكا اللاتينية . في هذا البحث، سنتناول بالدراسة الاطار النظري للإصلاحات الاقتصادية، ثم نحاول التفرقة بين اصلاحات الجيل الاول واصلاحات الجيل الثاني وربطها بالتنمية المستدامة في الجزائر، مع عرض لبعض الآثار الاقتصادية والاجتماعية لتطبيق برامج الاصلاح الاقتصادي في الجزائر للفترة من 1990 الى 2010. The subject of economic development has received a great deal of attention in order to know its sources, methods of achieving them, how they are sustainable, the factors supporting them and their relation to economic reforms. This interest has been reinforced by the adoption of the majority of developing countries to shift from the central economy to the market economy as an alternative to sustainable development. Over time, economic policies and programs linked to the external debt crisis emerged in 1982 through the declaration of Mexico and some Latin American countries. In this paper, we will examine the theoretical framework of economic reforms and then try to distinguish between the first generation reforms and the second generation reforms and their linkage to sustainable development in Algeria.
مقال
Keywords: الاصلاح الاقتصادي، اصلاحات الجيل الاول، اصلاحات الجيل الثاني، التنمية المستدامة; Economic Reform, First Generation Reforms, Second Generation Reforms, Sustainable Development